A comparison of methods for evaluating schools with respect to growth of students in subpopulations in three-level models. Issue 1 (2nd January 2023) - Liu, Yixing; Levy, Roy; Yel, Nedim; Schulte, Ann C.
ABSTRACT: Although there is recognition that there may be differential outcomes for groups of students within schools, examination of outcomes for subgroups presents challenges to researchers and policymakers. It complicates analytic procedures, particularly when the number of students per school in the subgroup is small. We explored five alternatives for applying a three-level multilevel growth modeling framework to examine school-level achievement for a select subgroup of students (students with disabilities) using a large longitudinal database tracking reading achievement. The alternatives vary in terms of use of subgroup only or all student data, use of student-level predictors, and method of linking student or school-level outcomes to school effectiveness indices. Correlations from .57 to .99 among alternatives suggest the choice of how to derive school-level outcomes for a subgroup has consequences for inferences about the school's effectiveness with the subgroup. Researchers' assumptions and data available should guide the selection of an approach.